2018
DOI: 10.4028/www.scientific.net/ssp.280.9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Magnetoelectric Effect in the Bi-Layer Plate Structure

Abstract: Recently, the magnetoelectric (ME) effect is widely studied to apply in sensing applications. This paper proposes the investigation of ME effect in the bi-layer plate structure, which is the structure that allows deformation in the thickness direction. Mathematical models of the ME coefficients are developed using the constitutive equations of magnetostrictive and piezoelectric. Two modes of interest include longitudinal-transverse (L-T) and transverse-transverse (T-T) modes. Applying the models to the nanolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Research on magnetoelectric (ME) materials has been growing dramatically owing to the material's potential for high frequency applications such as magnetic sensing in memory or storage devices and current-to-voltage conversion Vopsaroiu et al (2007); Palneedi et al (2006); Choowitsakunlert et al (2014); Nan et al (2008). The ME material is made of multiferroic composites that possess direct and converse ME coupling effects, which are the induction of electric polarization by the magnetic field and the induction of magnetization by the electric field, respectively Palneedi et al (2006); Saengow et al (2018); Wang et al (2010). The ME material can be formed as a single-phase structure or a heterostructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on magnetoelectric (ME) materials has been growing dramatically owing to the material's potential for high frequency applications such as magnetic sensing in memory or storage devices and current-to-voltage conversion Vopsaroiu et al (2007); Palneedi et al (2006); Choowitsakunlert et al (2014); Nan et al (2008). The ME material is made of multiferroic composites that possess direct and converse ME coupling effects, which are the induction of electric polarization by the magnetic field and the induction of magnetization by the electric field, respectively Palneedi et al (2006); Saengow et al (2018); Wang et al (2010). The ME material can be formed as a single-phase structure or a heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…There were several studies on developing mathematical models of the ME coefficient of the nano heterostructures with different input-output field orientations and operating modes such as L-T (longitudinal-transverse) and T-T (transverse-transverse) modes with bar and plate structures, respectively Vopsaroiu et al (2007); Saengow et al (2018); Wang et al (2010); Saengow and Silapunt (2020). These models were developed under the low frequency (f!0) approach, to reduce complexity of the modeling Vopsaroiu et al (2007); Saengow et al (2018). It was shown that that the L-T mode bar structure exhibits higher ME coefficient and offers more flexibility in the structure design, compared to the plate structure Saengow and Silapunt (2020).…”
Section: Introductionmentioning
confidence: 99%